Effect of Low Energy Laser on the Healing of Tooth Extraction Wound: (Histological Study in Rat) - alwattar, Warkaa mahmood (Iraqi Journal of Laser, 2021)
Aims: This study was done to investigate the effect of low energy laser therapy on bone healing at the extraction site. Materials and methods:(24) male albino rats were exposed to the extraction procedure of the maxillary first molar on the first day of a seven day experiment and these animals were divided into two main groups; the control group and the laser group. The laser experiment involved using (Ga-As infrared diode laser) from optodent by directing the probe over the extraction site. The control group consisted of 4 rats, and the laser group was subdivided into 5 subgroups of 4 rats each. The laser dose was as follows: B1: a single dose of 5 minutes immediately after extraction., B2: a single dose of 35 minutes immediately after extraction., B3: 7 doses for 7 days as 5 minutes /day from day 1-7., B4: 3 doses for 3 days as 10 minutes /day at days 1, 2, 3., B5: 3 doses for 3 days as 10 minutes/day at days 4, 5, 6., The specimens were prepared for histological study, then examined under light microscopy, Results: They revealed a difference in the rate of bone healing between the control and laser groups and   multiple doses of low energy laser were effective in enhancing bone formation than the single dose,  showing that retardation in the healing may be due to the anti-inflammatory effect of the  laser or due to upset of inflammation by mast cells. The healing of the bone in (B5) group was much prominent than in other groups. Conclusions: low energy laser may be beneficial in the enhancement of healing which will minimize the infection, and reduce patient suffering and the incidence of post-extraction complications.